A Scientific Overview of Epidemiology in Colombia, 2023: A Brief Bibliometric Analysis: Perspectiva científica de la epidemiología en Colombia, 2023: Un breve análisis bibliométríco - Serna-Trejos, Juan Santiago (2023)
In Colombia, epidemiological research focuses on analyzing the effects left by the coronavirus across broad areas related to its spread. There is also a marked trend in research on microbiology and antimicrobial resistance, as well as on tropical zoonotic diseases such as dengue, which has a high prevalence and incidence in the country.